Evaluating Inclusive EFL Instruction for Visually Impaired Students in Beninese Secondary Schools - Toboula, Coffi Martinien Zounhin; Hounnou, Azoua Mathias; Videkon, Bidossessi Moïse (ELE Reviews: English Language Education Reviews, 2024)
Teaching English as a Foreign Language (TEFL) in an inclusive classroom with visually impaired and able-bodied students presents unique challenges. In particular, appropriate teaching and assessment strategies are critical in ensuring equitable education. This mixed-methods study, conducted at CEG2 Abomey in the Zou Region of Benin, aimed to develop an effective pedagogical approach to address these challenges. The research involved 200 students (57 visually impaired and 143 sighted) and seven teachers. Quantitative data were gathered through questionnaires, while qualitative data were collected through focus group discussions and classroom observations. Using descriptive statistical analysis and inductive method, the study identified a pressing need for reliable and objective assessment methods and teaching strategies to support visually impaired and sighted students. Despite these findings, the study anticipates potential challenges in implementing such approaches. Recommendations and suggestions have been made to address these difficulties and enhance TEFL education in inclusive classrooms.